Avaliação ambiental: uma percepção dos servidores da Secretaria da Fazenda do Estado do Ceará - Sá, Yolita de Araújo (2012)
This scientific work was to subject the environment. The topic has been widely debated by governments and society by engaging questions that pertain to life not only of human beings but all living beings and the preservation of natural resources. The research aimed to evaluate the public server packed in Finance Department of the State of Ceará from two assumptions: perceptions of the public official in relation to Environmental Responsibility and the role of the state to environmental issues. Given the importance of conservation of natural resources and assets through the administrative machinery, empirical research sought to understand the profile, the level of knowledge, the degree of importance, interests, expectations and situations experienced by the server as part of your work routine and associate them with the aspects related to perception. Therefore, the methodology made use of the technique of questionnaires, which were delivered in print to 149 respondents, distributed across servers Farmers and outsourced service providers: research subjects. The study aimed to describe the function of specific population sociodemographic characteristics, using sampling technique given its representative character. The research strategy took advantage of approaches like quantitative-descriptive to assess opinions and perceptions of the public official, employing scales that allowed the quantification, with a view to applying the statistical method. The literature review included authors who treated multidisciplinary subjects such as social responsibility, environmental education and sustainability, beyond reading of institutional documents to substantiate the theoretical study, reinforcing the assumptions that support the object of the search. The results validate the two hypotheses about the perception about the server environment. The public official is indifferent to this question because there is low environmental awareness in the public sphere where it is inserted, but recognizes the existence of environmental problems. It also recognizes the need for their participation as subject to change. Similarly, a State recognizes silent on social and environmental programs, although the assign responsibility for developing and implementing public policy environment. In this sense, the perception of environmental fazendário server is compromised because there is a sense of continuity. Given these considerations, it was suggested the implementation of environmental education programs as a way to stimulate and encourage environmental best practice in public administration.